Quercetin inhibits truncated isoform of dopamine- and cAMP-regulated phosphoprotein as adjuvant treatment for trastuzumab therapy resistance in HER2-positive breast cancer - Han-Sheng Chang; Tzu-Chun Cheng; Shih-Hsin Tu; Chih-Hsiung Wu; You-Cheng Liao; Jungshan Chang; Min-Hsiung Pan; Li-Ching Chen; Yuan-Soon Ho (Food Science and Human Wellness, 2024)
Trastuzumab resistance is one of the causes of poor prognosis in patients with human epidermal growth factor receptor 2 (HER2)-positive (HER2+) breast cancer (BC). The truncated isoform of dopamine- and cAMP-regulated phosphoprotein (t-DARPP) has been reported to be involved in trastuzumab therapy resistance and promoting tumor progression. To evaluate the t-DARPP expression in BC, paired tumors and surrounding normal tissues were analyzed by real-time polymerase chain reaction and confirmed higher DARPP-32 kDa family mRNA expression in HER2+ BC tumor tissues. We established 2 patient-derived xenografts (PDX) mice models to test the efficacy of trastuzumab, named model 1 (non-responder) and model 2 (responder). t-DARPP and p95-HER2 protein-protein interactions were detected in PDX tumor tissue from non-responders using Förster resonance energy transfer assays. Instead, there is no response from the responder. Furthermore, mechanistic studies using transwell and western blot assays demonstrated that t-DARPP could upregulate epithelial-mesenchymal transition signaling proteins, enhance p95-HER2 expression and promote cell migration. We found that quercetin effectively reduced t-DARPP expression in HER2+ BC cells. In t-DARPP ShRNA-suppressed cells, quercetin synergistically enhanced trastuzumab-induced apoptotic cell death and G2/M phase arrest. In conclusion, the combination of quercetin and trastuzumab treatment by targeting t-DARPP in HER2+ BC patients has the potential as a biomarker for mitigating drug resistance.